2010
DOI: 10.1371/journal.pone.0010672
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interaction and Cross-Regulation of Three Mycobacterium tuberculosis RelBE Modules

Abstract: RelBE represents a typical bacterial toxin-antitoxin (TA) system. Mycobacterium tuberculosis H37Rv, the pathogen responsible for human tuberculosis, contains three RelBE-like modules, RelBE, RelFG, and RelJK, which are at least partly expressed in human macrophages during infection. RelBE modules appear to be autoregulated in an atypical manner compared to other TA systems; however, the molecular mechanisms and potential interactions between different RelBE modules remain to be elucidated. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
88
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 27 publications
2
88
0
Order By: Relevance
“…12,45,55,56 Recent studies have demonstrated that TA-II systems can affect positively or negatively the expression of other TA-II modules. 39,57,58 However in these studies, only changes in steady-state RNA levels have been shown, and RNA synthesis (transcription) and RNA stability effects cannot be distinguished. In our experiments, direct RNA stability measurements rule out stability effects of MazE and MazEF on RatA, since the RatA half-life is independent of MazE and MazEF levels.…”
Section: Discussionmentioning
confidence: 99%
“…12,45,55,56 Recent studies have demonstrated that TA-II systems can affect positively or negatively the expression of other TA-II modules. 39,57,58 However in these studies, only changes in steady-state RNA levels have been shown, and RNA synthesis (transcription) and RNA stability effects cannot be distinguished. In our experiments, direct RNA stability measurements rule out stability effects of MazE and MazEF on RatA, since the RatA half-life is independent of MazE and MazEF levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, 30 out of 38 putative TA systems from M. tuberculosis were functional when expressed in E. coli (61). Of the nine MazF homologs identified in M. tuberculosis, seven have been studied and shown to cause growth arrest when expressed in E. coli (49,62,63 (64,65). Further worked showed that expression of the RelE2 toxin in M. tuberculosis induced the formation of drug-specific persisters in vitro; however, deletion of relE2 did not affect the level of persisters of M. tuberculosis in rifampin-treated mice ruling out a role for relE2 in the generation of bacilli that survive multidrug therapy (66).…”
Section: Discussionmentioning
confidence: 99%
“…Surface Plasmon Resonance Analysis-Interaction between MsDisA and MsRadA in vitro was analyzed on a BIAcore 3000 instrument (GE Healthcare) as described previously (18,19). Briefly, the purified GST-tagged MsRadA fusion protein, to be used as the ligand, was diluted in HBS buffer (10 mM Hepes (pH 7.4), 150 mM NaCl, 50 M EDTA, 0.005% BIAcore surfactant P20).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial Two-hybrid Assay-Bacterial two-hybrid analysis was carried out according to the procedures described in a previous report (19). pBT and pTRG vectors containing the disA and radA genes were generated.…”
Section: Methodsmentioning
confidence: 99%